Potential opportunities and strategy of Building Information Modelling (BIM) in Malaysian infrastructure construction - Asmawan Mohd Sarman; Lim, Chung Han; Allan Lumberio Lim; Elis Mardzianah Mazlan; Muhammad Muizzuddin Mukhtar (e-VIBS, Faculty of Science and Natural Resources, 2022)
This study mainly identifies the potential, opportunities and strategy of Building Information Modelling (BIM) in Malaysian infrastructure construction. The main objective of this study is to identify the barriers and strategies to overcome the implementation of BIM in the Malaysian construction industry, Sabah to be specific. The industry personnel have conducted an online survey through Google Forms. SPSS identified barriers, and correlation analysis was carried out. Besides, a bridge representing the infrastructure component is modelled to determine the interoperability of the available software in the market. Throughout the survey, it is evident that several issues that stall the implementation of BIM in the Malaysian construction industry are required to be addressed. While for the modelling part, software interoperability from different developers arises during the modelling process, which could also be a barrier in this topic.